Measurement of cellular forces at focal adhesions using elastic micro-patterned substrates - Schwarz, Ulrich S. (Materials science & engineering. C, Materials for biological applications, 2003)
Mechanical force is known to play an important role in the regulation of cellular behaviour, including adhesion, motility, differentiation and proliferation. For stationary, mechanically active cells like fibroblasts, adhesion to flat substrates occurs mainly at sites of focal adhesions, which are micron-sized protein aggregates at the plasma membrane, which on the cytoplasmic side connect to the actin cytoskeleton. In recent years, evidence has been growing that focal adhesions act as mechanosensors which convert mechanical force into biochemical signalling. We have investigated the relationship between force and aggregation at focal adhesions by a new method which combines elastic micro-patterned substrates (to record substrate deformation), fluorescence labelling of focal adhesion proteins (to monitor aggregation) and numerical solution of the inverse problem of linear elasticity theory (to calculate forces at focal adhesions). We have found that force correlates linearly with lateral size of aggregation, with a stress constant of 5.5 nN/μm2. This finding indicates that mechanosensing involves regulation of aggregation.
Published online: 19 December 2002
Gesehen am 15.12.2017